Assessment of the morphometry of saccular otoliths as a tool to identify triplefin species (Tripterygiidae) - Avigliano, Esteban (2015)
In the present work we describe nine saccular otolith morphometric indices (circularity, rectangularity, aspect ratio, percentage of the otolith surface occupied by the sulcus, percentage of the sulcus length occupied by the cauda length and ostium length, otolith length relative to the length of the fish, rostrum aspect ratio and percentage of the rostrum length occupied by the otolith length) of 41 species of the Tripterygiidae family collected mainly from New Zealand, Australia, Chile, South Africa, Mediterranean Sea and North America. The principal component of analysis showed that the indices that best explain the variability between species were related to sulcus and rostrum morphometry. According to cluster analysis, otolith morphometry could reflect the diversity of microenvironments for some genera such as Notoclinops and Forsterygion, while this does not happen to genera like Enneapterygius and Ruanoho. The discriminant analysis showed that the species Helcogrammoides cunninghami, Karalepis stewarti, Lepidoblennius haplodactylus, Notoclinus compressus, Ucla xenogrammus can be discriminated by using the morphometric indices. Two new indices related to the sulcus that were of great value for the discrimination of these species are described for the first time. This information will be a useful tool for palaeontological, taxonomic and trophic ecology studies.